Micro/Nanoscale Surface Modification of Ti6Al4V Alloy for Implant Applications - GÜLLÜOĞLU, ARİF NİHAT; DEMİRCİ, SELİM (SPRINGER, 2022)
In this study, micro- and nanosurface structures were fabricated by sandblasting (S), acid-etching (E), anodic oxidation (A), sandblasting/acid-etching (SE), sandblasting/anodization (SA) and sandblasting/acid-etching/anodization (SEA) processes on Ti6Al4V alloy in order to investigate apatite formation ability. The phase, morphology, topography, roughness and wettability properties of surfaces were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), surface profilometer and contact angle techniques. In vitro tests were performed in simulated body fluid (SBF) for 21 days. The results showed that the surface topography, roughness and wettability changed the Ca and P ion ratio. The SEA sample had high surface topography and the lowest contact angle value. The value of Ca/P ratio was 1.81 for SEA sample. The SEA sample showed the highest Ca/P ratio value which was close to theoretical value. Ca and P ion ratio value because of bioactive phases on the surfaces, high surface roughness and lower contact angle values as compared to other samples. The proposed methodology improves the apatite formation ability of Ti6Al4V alloys. Sandblasted/acid-etched/anodized surfaces can be an alternative to conventional sandblasted/acid-etched implant surfaces.
Keywords: apatite formation; bioactivity; micro; nanosurface; surface modification; Ti6Al4V; TI-6AL-4V ALLOY; COMPOSITE COATINGS; APATITE FORMATION; TITANIUM; TIO2; WETTABILITY; BIOACTIVITY; ROUGHNESS; OSSEOINTEGRATION; MORPHOLOGY